2016
DOI: 10.1590/0004-282x20160139
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of the complement 5 gene is associated with large artery atherosclerosis stroke in Chinese patients

Abstract: The complement system has been confirmed to play an increasingly important role in ischemic stroke (IS). This study aimed to determine whether the single-nucleotide polymorphism of the complement 5 (C5) gene independently influences the occurrence, severity, and long-term outcome of IS in Chinese patients. Methods C5 rs17611 genetic variants were investigated in 494 IS patients and 330 control individuals .Ischemic stroke was classified into subtypes and patients were assessed 90 days post-stroke with the mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…These include ten proteins (APCS, APOM, C1qA, C4BPA, CBP2, F2, FBLN1, IGKV1D-12, KLKB1, SERPINF2) that differentiate the cardioembolic vs. large-vessel stroke, six other proteins (AMBP, APOA4, FCN3, ITIH4, LBP, PF4) that differentiate the cardioembolic vs. lacunar stroke, and another six proteins (APOL1, C5, GPX3, GSN, H2AFJ, IGK) that differentiate the large-vessel vs. lacunar stroke (Table 3, Figure 3B). To the best of our knowledge, with the exception of C5, known to be associated with large-vessel stroke in a Chinese population [18], these differentiating proteins, weree not previously associated with a specific subtype of the ischemic stroke. These findings raise a possiblity that the ischemic stroke subtype-specific proteins can be exploited, most likely as a panel, in diagnosis and prognosis of outcomes, and possibly therapeutic interventions.…”
Section: Discussionmentioning
confidence: 99%
“…These include ten proteins (APCS, APOM, C1qA, C4BPA, CBP2, F2, FBLN1, IGKV1D-12, KLKB1, SERPINF2) that differentiate the cardioembolic vs. large-vessel stroke, six other proteins (AMBP, APOA4, FCN3, ITIH4, LBP, PF4) that differentiate the cardioembolic vs. lacunar stroke, and another six proteins (APOL1, C5, GPX3, GSN, H2AFJ, IGK) that differentiate the large-vessel vs. lacunar stroke (Table 3, Figure 3B). To the best of our knowledge, with the exception of C5, known to be associated with large-vessel stroke in a Chinese population [18], these differentiating proteins, weree not previously associated with a specific subtype of the ischemic stroke. These findings raise a possiblity that the ischemic stroke subtype-specific proteins can be exploited, most likely as a panel, in diagnosis and prognosis of outcomes, and possibly therapeutic interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Proteins act on pathogen opsonization in a cascade reaction and induce inflammation, which activates immune cells against the invading agent and assist in maintaining host homeostasis ( 44 ). Studies have confirmed that genetic mutations in complement genes, as well as modifications in their expression levels, are associated with development of several human disorders, such as schizophrenia ( 45 ), age-related macular degeneration ( 46 ), Alzheimer’s disease ( 47 ), myocardial infarction ( 48 ), and stroke ( 49 ). In addition, these events were also interrelated with susceptibility to several bacterial and viral infectious diseases, such as meningitis ( 50 , 51 ), leprosy ( 52 ), hepatitis B ( 53 ), and diseases caused by trypanosomatids: CD ( 22 ), VL ( 36 ), and CL ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“… 43 Other studies indicated that rs17611, a missense polymorphism leading to a V802I change in C5, was associated with elevated C5a production, increased susceptibility to large artery atherosclerosis stroke, and poor cardiovascular outcome. 44 , 45 However, no current studies have explored the clinical relationship of C5 SNPs with the susceptibility and clinical prognosis of sepsis. In this study, our results indicated that rs2269067 polymorphism exerted protective effect against sepsis susceptibility, as indicated by significantly lower frequencies of the GC/CC genotypes or C allele in sepsis patients than in healthy controls.…”
Section: Discussionmentioning
confidence: 99%